Recurrent purulent meningitis in a patient with Bruton's disease - Kanra, Güler; Arslan, Şükrü; Ergin, Murat; Tarım, Ömer; Yurdakök, Murat; Seçmeer, Gülten; Sanal, Özden; Ersoy, Fügen; Oran, Olcay (The Turkish Journal of Pediatrics, 1987)
A five-year-old boy with Bruton's disease and recurrent pyogenic meningitis is presented, and the importance of the evaluation of patients with recurrent meningitis for immunodeficiency diseases is emphasized.
Keywords: Bruton's disease; hypogammaglobulinemia; recurrent purulent meningitis